Causes of blindness in rural Myanmar (Burma): Mount Popa Taung-Kalat Blindness Prevention Project - Arie Y Nemet (Dove Medical Press, 2009)
Arie Y Nemet1, Pinhas Nemet2, Geoff Cohn3, Gina Sutton, Gerald Sutton4, Richard Rawson41Department of Ophthalmology, Sydney Hospital and Sydney Eye Hospital, Sydney, Australia; 2Sackler School of Medicine, Tel-Aviv University, Israel; 3Departments of Ophthalmology, University of New South Wales, Sydney, Australia; 4Department of Ophthalmology, University of Sydney, AustraliaPurpose: This study is a review of the major causes of visual impairment (VI) and severe visual impairment/blindness (SVI/BL) in Mount Popa Taung-Kalat, a rural region in Myanmar (Burma).Methods: A review of our clinical records of consecutive patients attending clinics was conducted. Participants of all ages (n = 650) of the population of Mount Popa Taung-Kalat and villages in its vicinity underwent ophthalmic interview and a detailed dilated ocular evaluation by trained Australian ophthalmologists and ophthalmic nurses. This evaluation included anterior segment examination with a slit lamp, intraocular pressure recording, and direct or indirect ophthalmoscopy. VI and SVI/BL were defined by the World Health Organization (WHO) criteria. Results: Six hundred fifty subjects were screened, with a mean age of 49.0 ± 20.6 years (range, 1–99). One hundred five patients (16.2%) were children (ages 1–18). Five hundred thirty-one eyes of the total 1,300 eyes (39.5%) had VI/SVI/BL, and 40 eyes of the children (38.1%) (average age 15.3 ± 13.3) had VI/SVI/BL. The leading causes of VI/SVI/BL were cataract with 288 cases (54.2%), glaucoma with 84 cases (15.8%), and corneal pathology with 78 cases (14.7%). Of all the VI/SVI/BL cases, 8.4% were preventable, 81.9% were treatable, and total of 90.5% were avoidable.Conclusions: In the current study, cataracts were the major cause of blindness and visual impairment, and most of the ophthalmic pathology causing blindness is avoidable. These results highlight the lack of basic ophthalmologist eye care and optician resources in rural regions in Myanmar.Keywords: blindness, visual loss, cataract, Myanmar, Burma, epidemiology study